The potential of bacterial anti-phagocytic proteins in suppressing the clearance of extracellular vesicles mediated by host phagocytosis - Sun, Jiacong; Chen, Congcong; Pan, Pengpeng; Zhang, Keyi; Xu, Jinrui; Chen, Cheng (Frontiers in Immunology, 2024)
Extracellular vesicles (EVs), characterized by low immunogenicity, high biocompatibility and targeting specificity along with excellent blood-brain barrier permeability, are increasingly recognized as promising drug delivery vehicles for treating a variety of diseases, such as cancer, inflammation and viral infection. However, recent findings demonstrate that the intracellular delivery efficiency of EVs fall short of expectations due to phagocytic clearance mediated by the host mononuclear phagocyte system through Fcγ receptors, complement receptors as well as non-opsonic phagocytic receptors. In this text, we investigate a range of bacterial virulence proteins that antagonize host phagocytic machinery, aiming to explore their potential in engineering EVs to counteract phagocytosis. Special emphasis is placed on IdeS secreted by Group A Streptococcus and ImpA secreted by Pseudomonas aeruginosa, as they not only counteract phagocytosis but also bind to highly upregulated surface biomarkers αVβ3 on cancer cells or cleave the tumor growth and metastasis-promoting factor CD44, respectively. This suggests that bacterial anti-phagocytic proteins, after decorated onto EVs using pre-loading or post-loading strategies, can not only improve EV-based drug delivery efficiency by evading host phagocytosis and thus achieve better therapeutic outcomes but also further enable an innovative synergistic EV-based cancer therapy approach by integrating both phagocytosis antagonism and cancer targeting or deactivation.